Comparative study to evaluate the awareness about anemia and its complications, among undergraduate and postgraduate medical students- a cross sectional survey study - Patharkar, Jayant; Sattigeri, B. M.; Amane, H. S.; Brahmbhatt, S. V. (International Journal of Research in Medical Sciences, 2017)
Background: Anemia is a condition in which numbers of red blood cells or their oxygen carrying capacity is insufficient to meet the physiologic needs which vary by age, sex, altitude, smoking and pregnancy status. Iron deficiency anemia is the most common type of anemia in the world. Aim of the study was to compare and evaluate awareness about anemia and its complications among the undergraduate and postgraduate medical students. Methods: A prospective, cross sectional, questionnaire based, survey study was carried out at S.B.K.S. Medical institute and RC, Vadodara. The well-defined, structured questionnaire was prepared, distributed and collected when it was duly filled by undergraduate and postgraduate students. The questionnaire was mainly based upon basic knowledge of anemia, its investigations, treatment, and complications. The answers were evaluated in a structured format and further depending on the scores the participants were grouped as poor (<50%), average (50%-70%) and good performers (>70%). Later, it was subjected to Chi-square test and p value <0.05 were considered to be significant. Results: This study shows that the basic knowledge of anaemia and knowledge pertaining to treatment of anaemia is lacking in undergraduate students as compared to postgraduate students. However it was observed in both the study groups that knowledge about various aspects of anaemia is not optimal. Conclusions: It is a need of hour to impart knowledge of common disorders including anemia to both undergraduate and postgraduate students for the larger benefit of society.